The Influence of Digital Literacy, Educational Background, and Environment on Youth Entrepreneurial Decisions, Benowo District, Surabaya - Andrean, Jordan (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to determine the effect of Digital Literacy, Education Level, and Environment on Youth Entrepreneurial Decisions, Benowo District, Surabaya. The sample used in this study were 100 youth respondents in the sub-district of Benowo Surabaya with purposive sampling technique. This study was analyzed using the SmartPLS version 3 software. The results of this study indicate that digital literacy and the environment have a positive and significant influence on entrepreneurial decisions. While the level of education does not have a significant influence on entrepreneurial decisions.